2019
DOI: 10.1371/journal.pone.0222721
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the blood-brain barrier in postoperative delirium patients, referring to the axonal damage biomarker phosphorylated neurofilament heavy subunit

Abstract: BackgroundDelirium is the most common postoperative complication of the central nervous system (CNS) that can trigger long-term cognitive impairment. Its underlying mechanism is not fully understood, but the dysfunction of the blood-brain barrier (BBB) has been implicated. The serum levels of the axonal damage biomarker, phosphorylated neurofilament heavy subunit (pNF-H) increase in moderate to severe delirium patients, indicating that postoperative delirium can induce irreversible CNS damage. Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…Serum NfL levels in delirium in hip fracture patients were 1.7-fold higher than in controls (94 vs. 54 pg/ml) ( Halaas et al, 2018 ) and plasma NfL was associated with delirium severity ( Fong et al, 2020 ) independent of changes in inflammation ( Casey et al, 2019 ). In addition to elevated NfL, higher serum pNfH levels also correlated with more severe postoperative delirium ( Inoue et al, 2017 ; Mietani et al, 2019 ). These results suggests NfPs can be sensitive markers of neuronal injury associated with delirium.…”
Section: Properties Of Neurofilaments Relevant To Their Use As Biomarkersmentioning
confidence: 99%
“…Serum NfL levels in delirium in hip fracture patients were 1.7-fold higher than in controls (94 vs. 54 pg/ml) ( Halaas et al, 2018 ) and plasma NfL was associated with delirium severity ( Fong et al, 2020 ) independent of changes in inflammation ( Casey et al, 2019 ). In addition to elevated NfL, higher serum pNfH levels also correlated with more severe postoperative delirium ( Inoue et al, 2017 ; Mietani et al, 2019 ). These results suggests NfPs can be sensitive markers of neuronal injury associated with delirium.…”
Section: Properties Of Neurofilaments Relevant To Their Use As Biomarkersmentioning
confidence: 99%
“…Non-specific markers of systemic inflammation, such as CRP, IL-6, IL-1B, or TNF-a, in the blood or CSF are frequently associated with delirium but poorly predict POCD [ 63 66 ]. Conversely, biomarkers of neuronal damage, such as S100ß, NSE [ 67 ], or phosphorylated neurofilament heavy subunit, are more consistently associated with POD and POCD [ 68 ]. In 2012, one study explored ICU survivors in a pilot study combining diffusion tensor imaging MRI, acute delirium monitoring, and cognitive outcomes in 47 patients evaluated after 3 and 12 months of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the diagnosis of delirium is clinically based and depends on the absence or presence of certain features. As delirium appears to be associated with permanent encephalopathy with neuronal damage and/or dysfunction, several studies have investigated NFs as potential new biomarkers of neuroaxonal damage in delirium patients [156][157][158][159][160][161]. In a recent prospective, pilot observational study, Ehler and colleagues [161] demonstrated, using ELISA, that plasma NF-L levels increased in sepsis patients over time and remained stable in patients without sepsis.…”
Section: Deliriummentioning
confidence: 99%